Perancangan Aplikasi Administrasi SPP Online Berbasis Web Pada Sekolah Dasar - Nungky Septia Kurnicova; Sri Wahyuni Nainggolan; Tasya Basalia Sihombing; Errissya Rasywir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to design a web-based online tuition fee administration application for use in Adhyaksa Elementary School located in Jambi City. The development of this application aims to enhance the efficiency and effectiveness of managing tuition fee administration and increase parental involvement in the payment process. The research will utilize a software development research method, comprising phases of needs analysis, application design, implementation, and testing. Data will be collected through interviews with the school authorities and relevant literature study concerning tuition fee administration and web-based applications. The results of the needs analysis will be used to design the online tuition fee administration application that suits the requirements and characteristics of Adhyaksa Elementary School in Jambi City. Subsequently, the application will be implemented using web technologies and programming languages that are appropriate for the purpose. In conclusion, the research has successfully developed the Web-Based Online Tuition Fee Administration Application for Adhyaksa Elementary School in Jambi City. The system functions well and includes features such as generating tuition fee invoices, recording fee payments, and sending payment notifications to parents/guardians.